Paroxysmal Atrial Fibrillation in Cryptogenic Stroke Patients With Major-Vessel Occlusion - Doijiri, Ryosuke; Yamagami, Hiroshi; Morimoto, Masafumi; Iwata, Tomonori; Hashimoto, Tetsuya; Sonoda, Kazutaka; Yamazaki, Hidekazu; Koge, Junpei; Kimura, Naoto; Todo, Kenichi (Frontiers in Neurology, 2020)
Background and Purpose: To determine whether acute major-vessel occlusion (MVO) predicts atrial fibrillation (AF) in cryptogenic stroke (CS) patients, we analyzed the association between acute MVO and AF detected by insertable cardiac monitoring (ICM). Methods: We conducted a retrospective, multicenter, observational study of patients with CS who underwent ICM implantation between October 2016 and March 2018. In this analysis, we included follow-up data until June 2018. We analyzed the association of MVO with AF detected by ICM. Results: We included 84 consecutive patients with CS who underwent ICM implantation. The proportion of patients with newly detected AF by ICM was higher in patients with MVO than in those without (41% [12/29] vs. 13% [7/55], p < 0.01) within 90 days of ICM implantation. The MVO was associated with AF after adjustment for each clinically relevant factor. Conclusions: MVO was independently associated with AF detection in patients with CS, which suggests that MVO may be a useful predictor of latent AF. It is therefore essential to actively assess latent AF in patients with CS presenting with MVO.